Mapping Technology Acceptance Research in MSMEs - Rahmanda Putra, Rifki; Rahmat Jaya, Nono; Setiawan, Adi (International Journal of Engineering, Science and Information Technology, 2025)
MSMEs contribute significantly to the Indonesian economy but often face challenges in technology adoption. This research identifies factors and barriers to technology acceptance in MSMEs, aims to formulate support strategies, and highlights the role of all in increasing technology acceptance. The results are expected to provide practical solutions for the MSME sector. This research uses qualitative methods with bibliometric techniques using the Vosviewers application. Searches used keywords such as external stimuli, Obstacle, Opportunity, Challenge, Cognitive response, and Readiness. The idea was to search for articles via Publish or Perish with 762 articles, which were then processed using VosViewers. The analysis results found that scientific mapping and the possibility of future research regarding technology acceptance could be used as a recommendation variable for future researchers as a reference for subsequent articles.